(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Ytterbium (Yb)-doped of Bi(Pb)-2223 with varying concentration was prepared by co-precipitation (COP) and solid state reaction (SSR) to produce high density and low density samples respectively. In this work, the samples were characterized by X-ray diffraction analysis (XRD) and resistivity measurement system. Substitution of Yb in Bi(Pb)-2223 decreased the volume percentage of 2223 phase, the length of c-parameter, TC and JC towards higher concentration of Yb. The crystallographic structure is tetragonal in a low concentration of Yb but changes to orthorhombic at higher Yb-doped. The high-density samples have a higher volume percentage of 2223 phase and critical temperature, TC for the same concentration of Yb compared to low-density samples. However, the critical current density, JC in low-density samples is higher compared to high-density samples due to the large surface area in a porous structure made by sucrose. The large surface area favors improving the grains connectivity during the sintering process.Â